fMRI of Cocaine Self-Administration in Macaques Reveals Functional Inhibition of Basal Ganglia - Mandeville, Joseph B (Nature Publishing Group, 2011)
Disparities in cocaine-induced neurochemical and metabolic responses between human beings and rodents motivate the use of non-human primates (NHP) to model consequences of repeated cocaine exposure in human subjects. To characterize the functional response to cocaine infusion in NHP brain, we employed contrast-enhanced fMRI during both non-contingent injection of drug and self-administration of cocaine in the magnet. Cocaine robustly decreased cerebral blood volume (CBV) throughout basal ganglia and motor/pre-motor cortex and produced subtle functional inhibition of prefrontal cortex. No brain regions exhibited significant elevation of CBV in response to cocaine challenge. Theses effects in NHP brain are opposite in sign to the cocaine-induced fMRI response in rats, but consistent with previous measurements in NHP based on glucose metabolism. Because the striatal ratio of D2 to D1 receptors is larger in human beings and NHP than rats, we hypothesize that the inhibitory effects of D2 receptor binding dominate the functional response in primates, whereas excitatory D1 receptor stimulation predominates in the rat. If the NHP accurately models the human response to cocaine, downregulation of D2 receptors in human cocaine-abusing populations can be expected to blunt cocaine-induced functional responses, contributing to the weak and variable fMRI responses reported in human basal ganglia following cocaine infusion.